Climate-smart agro-hydrological model for the assessment of future adaptive water allocation for Tanjong Karang rice irrigation scheme - Ismail, Habibu (2020)
Agro-hydrological water management framework helps to integrate expected planned management and expedite regulation of water allocation for agricultural production. Low production is not only due to the variability of available water during the crop growing seasons, but also due to poor water management decisions, such as not considering the available water for irrigation. Climate-smart agro-hydrological model can be a robust solution for wise water management decisions in a large-scale irrigation scheme to cope with the risk of water and food security under the new realities of climate change. The Tanjung Karang Rice Irrigation Scheme has yet to model agro-hydrological systems for effective water distribution under climate change impacts. The study aimed to develop a climate-smart agro-hydrological model in the context of adaptive water allocation under the risk of climate change for a large-scale rice irrigation scheme. In this study, daily climate variables for baseline (1976-2005) and future 2020s (2010-2039), 2050s (2040-2069) and 2080s (2070-2099) periods were extracted for ten global climate models (GCMs) under three Representative Concentration Pathways (RCPs) scenarios (RCP4.5, RCP6.0, and RCP8.5). Climate variables then downscaled to a local station using Climate-smart Decision Support System (CSDSS) in the MATLAB environment. Two hydrological models Soil Water Assessment Tool (Arc-SWAT 2012) and Hydrologic Engineering Corps Hydrologic Modeling System (HEC-HMS 4.2) simulated climate change impacts on hydrological processes in Upper Bernam River Basin (UBRB). The Hydrologic Engineering Center’s River Analysis System (HEC-RAS 5.0) hydraulic model used to compute available discharges for the main water conveyance system from the Bernam River Headwork to Tengi River and at the key points in the main canal. The impact of climate change on potential basin streamflow was evaluated using the validated HEC- HMS model. Based on design parameters, the inflow and release patterns for the newly built reservoir were assessed with the need for irrigation water demand and available water for supply under future climate change. Finally, Climate-smart agro-hydrological model was developed using Excel-based Visual Basic for Application (VBA) to analyze and visualize climate and hydrological knowledge for wise adaptive water management practices under new climate change realities.